Efektivitas Media Pembelajaran Game Edukasi Berbasis Wordwall Dalam Meningkatkan Hasil Belajar Siswa Pada Materi Usaha Dan Energi Di SMA Negeri 8 Tidore Kepulauan - Muksin, Marwiya; Ali, Nursanti; Muhlis, Fahima (KUANTUM: Jurnal Pembelajaran dan Sains Fisika, 2025)
This study aims to determine the effectiveness of the Wordwall-based educational game as a learning media in improving students' learning outcomes on the topic of work and energy at SMA Negeri 8 Tidore Kepulauan. The issue addressed is the low physics learning outcomes due to the dominance of conventional teaching methods and the limited use of interactive media. This research employs a quantitative approach with a quasi-experimental design using a pretest-posttest control group model. The sample consists of two classes: the experimental class using Wordwall media and the control class using traditional whiteboard-based teaching. The research instrument was a multiple-choice test consisting of 30 validated items. The results of the study show that the average post-test score in the experimental class increased significantly from 44.32 to 80.96, while in the control class it only increased from 61.86 to 67.71. The t-test results indicate that the t-count value of 3.271 is greater than the t-table value of 1.675, with a significance value of 0.002 < 0.05. Therefore, there is a significant difference in student learning outcomes between the experimental class and the control class. Therefore, it can be concluded that the use of Wordwall-based educational game media is effective in improving students' learning outcomes on the topic of work and energy. Wordwall has been proven to enhance motivation, engagement, and conceptual understanding in a more interactive and enjoyable learning environment.